(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2023)
This research explains the origin and purpose of traditional tattooing in the culture of the Iban community in Sarawak. The tradition of tattooing is part of the culture of the Iban community, and is considered sacred because it is believed to connect the soul of the Iban community to their petara (god). This research used an overall qualitative approach. The data were obtained by conducting observation and interviews with informants who have expertise in the tattoo tradition. The study found that each tattoo motif of the Iban community has its own meaning and function for the group that owns it. This is because in the heritage belief of the Iban community, tattoos are a symbolic gift from petara for an achievement or success experienced in their daily life. Therefore, the tradition of tattooing is seen as a sacred and mystical cultural trait of the Iban community. The Iban community lives in a natural environment. For them, nature is used as a source of ideas and inspiration to produce tattoo motifs. This shows that the Iban community and nature have a close and mutually beneficial relationship. This phenomenon shows that the Iban community greatly appreciates nature, which serves as the main idea in shaping their cultural traditions. Through nature, the Iban community produces a tattoo that describes the nature and character of a person and has characteristics similar to the natural life in their community. Full text: PDF